ACADEMIC GOVERNANCE AT THE UNIVERSITY SALAH BOUBNIDER CONSTANTINE 3 - Soumia Bentahar; Amirouche Bouchelaghem; Rofia Abada (JURNAL EDUSCIENCE, 2023)
University governance seems to have undergone many changes, often associated with economic and/or political crises. Until the 1960s, universities were mostly "ivory towers" run by academics and designed for a specific social category, the elite. In the case of Algeria, it is the government that intervenes in the financing and management of higher education institutions. The idea of reforming the governance of academic institutions is not a passing fad or a project linked to a power process or a party or union agenda. This idea has emerged slowly, with the deepening disintegration of the university system from within and the current emergence of a global transformation movement at the top of various institutions. This work aims to present the main characteristics as well as the strategy of the reform of Higher Education in Algeria.Keywords: University governance, higher education, scientific research, strategy, reform.